Immobilization and electrochemical properties of anionic complexes on a V2O5/surfactant nanocomposite - da Silva, L. F.; Profeti, LPR; Stradiotto, Nelson Ramos [UNESP]; Oliveira, H. P. (Elsevier B.V., 2002)
in this work, we report a new way of modifying an electrode by combining the intrinsic conductivity property of vanadium pentoxide xerogel with its water insolubility in the presence of the cationic surfactant N-cetyl-N,N,N,trimethyl-ammonium bromide (CTA(+)Br(-)). The obtained hybrid compound enables the immobilization of electroactive anions such as hexacyanoferrate (III) ([Fe(CN)(6)](3-)) and its analogue pentacyanonitrosylferrate (II) ([Fe(CN)(5)NO](2-)), rather than cations. (C) 2002 Elsevier B.V. B.V. All rights reserved.